Re-imagining Indigenous Knowledge and Practices in 21st Century Africa : Debunking Myths and Misconceptions for Conviviality a (Book collections on Project MUSE., 2022)
This book is on the re-imagination of Indigenous Knowledge Systems (IKS) and practices in 21st century Africa.